Molecular characterization of fragrance-related transcripts in benzenoid/phenylpropanoid pathway of Vanda Mimi Palmer - Mohd Aiman, Barudin (2016)
Vanda Mimi Palmer (VMP) is a scented orchid that has received several international recognitions for its strong-sweet fragrance containing high percentage of benzenoids as well as phenylpropanoid compounds. Unfortunately, knowledge on the biosynthesis of benzenoids and phenylpropanoid compounds is still not fully-understood especially in Vandaceous orchid. Thus, this study was aimed to identify, isolate and molecular characterise potential transcripts that might be involved in the biosynthesis of benzenoids and phenylpropanoids in VMP. Screening of fragrance-related transcripts via cDNA-RDA approach has shown identification of partial sequences of phenylalanine ammonia lyase (VMPPAL) and S-adenosyl-L-methionine synthase (VMPSAMS) from VMP besides methionine synthases from Vanda Small Boy Leong (VSBLMS) and Vandachostylis Sri-Siam (VSSSMS). However, those transcripts were not further characterised due to their indirect involvement in final fragrance compounds biosynthesis. Thus, previously identified partial transcripts from floral cDNA library of VMP were isolated including 3-keto-acyl CoA thiolase (VMPKAT), benzoic acid/salicylic acid carboxyl methyltransferase (VMPBSMT), eugenol synthase (VMPEGS) and orcinol-O-methyltransferase (VMPOOMT), which resulted in the isolation of full ORF encoding 450, 378, 306 and 368 amino acids, respectively. All the transcripts were further characterised using molecular and bioinformatics approaches including domains identification, comparative modeling, molecular docking for substrates and ligands prediction as well as gene expression analysis using real-time RT-PCR. In this study, 3D-structural model was developed on those fragrance-related proteins for comparative modeling and molecular docking. Molecular docking on those proteins has shown their suitability towards specific substrates and ligands, reflecting their homologous putative functionality to fragrance-related proteins from other well-studied scented plants. However, gene expression analysis using real-time RT-PCR has shown that VMPKAT and VMPBSMT might be involved in benzenoids biosynthesis due to their up-regulated expression in floral tissues as well as developmentally-regulated expression pattern. Meanwhile for VMPEGS and VMPOOMT genes, their gene expression pattern might suggest their involvement as intermediates for biosynthesis of vanillin or other non-fragrance benzenoid and phenylpropanoid compounds, respectively. In conclusion, VMPKAT and VMPBSMT might be involved in fragrance benzenoid biosynthesis based on their functional catalytic prediction, up-regulated gene expression in floral compared to vegetative tissues and their developmentally-regulated expression pattern with the highest transcripts in fully-open flower.